Real-time shear wave elastography in measuring normal ileocolon intestinal wall stiffness using colonoscopy as reference: A single-center research - Shuo Wang; Shihui Li; Shuling Chen; Manying Li; Xiaoyan Xie; Mao Ren; Yujun Chen (European Journal of Radiology Open)
Purpose: To investigate the feasibility of real-time shear wave elastography (SWE) in evaluating intestinal wall stiffness, and to establish the threshold SWE value of normal intestinal wall and explore the influencing factors of intestinal SWE. Method: 659 subjects who underwent intestinal SWE and colonoscopy were retrospectively enrolled. The wall elasticity of colonoscopy-confirmed normal/abnormal intestinal segment was measured by transabdominal SWE. Measurement reliability was evaluated by the intraclass correlation coefficient (ICC). The threshold value of SWE in differentiating normal and abnormal intestine was determined using ROC curve analysis with the largest Youden index, and the diagnostic performance of this threshold was evaluated. We explored the effects of gender, age, depth and type of the targeted intestinal segment on the intestinal wall elasticity by t test and logistic linear regression analysis. Results: The technical success rate of SWE examination is 95.3 % (628/659). The mean SWE value of normal intestinal walls is (5.45 ± 1.34) kPa, which was significantly lower than that of abnormal ones (15.38 kPa±7.22, P < 0.001). Using 8.1 kPa as the threshold， the sensitivity and specificity were 93.5 % and 96.0 % with an AUC of 94.8 %. The overall ICC for SWE measurements was 0.933. Gender (ß=0.278, P = 0.013), depth (ß=0.220, P = 0.043) and type of the targeted segment (ß=0.522, P < 0.001) was associated with the SWE value of intestinal wall, but age was not (ß=0.050, P = 0.484). Conclusions: SWE is feasible in evaluating the stiffness of intestinal wall with high reliability. The SWE threshold value differentiating normal intestinal wall and abnormal intestinal wall is 8.1 kPa.